Anti-cancer properties of boswellic acids: mechanism of action as anti-cancerous agent - Trivedi, Vijay Laxmi; Soni, Ruchi; Dhyani, Praveen; Sati, Priyanka; Tejada, Silvia; Sureda, Antoni; Setzer, William N.; Faizal Abdull Razis, Ahmad; Modu, Babagana; Butnariu, Monica; Sharifi-Rad, Javad (Frontiers in Pharmacology, 2023)
With the advent of highly effective plant-based medications with few or no side effects, the use of phytomedicines against complex diseases such as cancer is becoming more widespread. The broadly recognized pentacyclic triterpenes known as boswellic acids (BAs) are derived from the oleogum resin, or frankincense, extracted from the plant species of the genus Boswellia. The frankincense mixture contains various BA types, each having a different potential and helping treat certain cancers. This review focuses on details regarding the traits of the BAs, their roles as anti-cancer agents, the mechanism underlying their activities, and the function of their semi-synthetic derivatives in managing and treating certain cancers. The review also explores the biological sources of BAs, how they are conserved, and how biotechnology might help preserve and improve in vitro BA production. The review concludes that the BAs and their semi-synthetic derivatives are effective against a broad spectrum of cancer cell lines. The detailed information in the review can be helpful for researchers to gain more information about BAs and BA-based medications for efficient and cost-effective cancer treatments.